A Syntactic Analysis Of Verb Phrases Found In Campus English Magazine Vol.54/ Xii/ 2013 (Using X-Bar Approach) - Hapsari, Luluk; , Mauly Halwat Hikmat, Ph. D; , Muamaroh, Ph.D (2014)
This research deals with analyzing Verb Phrase (VP) construction in English Magazine using X-bar approach by Andrew Radford (1988). This research aims at identifying the constituent of Verb Phrase and the functions of constituentss of verb phrase found in Campus English Magazine. This research applies descriptive qualitative method. In collecting the data, the writer uses documentation. The objects are verb phrase constituents. The analyses of data are sentences containing verb phrase construction used in Campus English Magazine Vol.54/XII/2013. The writer found 10 typical constructions of verb phrase from 66 data. The writer provides in the percentage for specific result. They are: (1) V"→ V + NP (Complement) in 37%, (2) V"→ V + NP (Complement) + PP (Adjunct) in 42%, (3) V"→ V + PP (Adjunct) in 9%, (4) V"→ V + PP (Adjunct) + PP (Adjunct) in 1, 5%, (5) V"→ AdvP (Adjunct) + V + NP (Complement) in 3 %, (6) V"→ M +V + NP (Complement) + NP (Complement) in 1, 5%, (7) V"→ M + V + AP (Adjunct) in 1, 5%, (8) V"→ M + V + AP (Complement) in 1, 5%, (9) V"→ M + V + AdvP (Adjunct) in 1, 5%, and (10) V"→ M + V + NP (Complement) + AdvP (Adjunct) in 1, 5%.